University-Based Adult Literacy in Ghana: School of Continuing and Distance Education (SCDE) Experiences - Mensah, D.O.; Biney, I.K. (MIER Journal of Educational Studies, Trends and Practices, 2016)
Ghana, Legon. Strategies to fight illiteracy and promote personal and national development are designed and implemented by many institutions, including universities. This is because disciplined, efficient and competent labour force is a priceless asset of a country. In the same manner, knowledgeable farmers and fishermen who efficiently adopt innovative, cultural and scientific practices on their farms and fishing expeditions to increase yields and forestall post-harvest losses are assets for Ghana. Industrial workers who can easily fix broken down plants and machines to keep them working day and night to increase productivity at workplaces are workers' Ghanaian economy needs. Educated electorates who cast their votes on the basis of issues are electorates this nation wants. The world now is a global village due largely to innovations in ICT, making lifelong learning and adult literacy very essential in personal and national development. In the light of this, well-planned and appropriately implemented University-Based Adult Literacy Programme as currently being executed by SCDE is a necessary prerequisite in building the needed human capital for Ghana's development. (PDF) UNIVERSITY-BASED ADULT LITERACY IN GHANA: SCHOOL OF CONTINUING AND DISTANCE EDUCATION (SCDE) EXPERIENCES. Available from: https://www.researchgate.net/publication/319205094_UNIVERSITY-BASED_ADULT_LITERACY_IN_GHANA_SCHOOL_OF_CONTINUING_AND_DISTANCE_EDUCATION_SCDE_EXPERIENCES [accessed Sep 26 2018].
Keywords: University-Based Adult literacy; Lifelong Learning; Human Capital; ICT and National Development